Damage model of unsaturated frozen soil while considering the influence of temperature rise under impact loading. (December 2021) - Fu, Tiantian; Zhu, Zhiwu; Ma, Wei; Zhang, Fulai
Abstract: Constitutive models and damage laws of frozen soil under high strain rates are crucial for the design of underground soil structures, and they lay an essential foundation for the research of instability phenomena in cold region engineering. The expansion and evolution of micro-defects and temperature damage are two basic mechanisms that control the macro and micro damage behavior of frozen soil. Considering frozen soil as a composite material, this study analyzes the damage mechanism of brittle materials subjected to impact loading. Finally, a dynamic model of unsaturated frozen soil under high pressure is established based on the complementary energy equivalence principle and Eshelby's equivalent inclusion theory. To analyze the effect of high-speed compression on the meso behavior of frozen soil, according to the Hugoniot energy theory, the evolution of temperature rise in the impact process is formulated. The results for frozen sandy soil confirm that the rate of temperature rise increases with the strain rate and has a significant weakening effect on the bearing capacity. Thus, the damage behavior of frozen soil changes according to different loading histories. Finally, based on the corresponding theoretical results, the mechanical response of frozen soil under different loading histories and the corresponding performance indicators are compared and analyzed. Highlights: Frozen soil is a rate-dependent and temperature-sensitive material. A meso-damage model of unsaturated frozen soil is established. Two different damage forms are introduced into the model. The evolution law of energy with loading history is analyzed. The theoretical results match well with the experimental ones.